Representation in Herbart and Freud and Its Place in Teaching - Ana María Fernández Caraballo (Universidade Federal do Rio Grande do Sul, 2013)
This article analyzes the different notions of representation in the philosophical and psychological theories of J. F. Herbart as well as ind the psychoanalytic theory of S. Freud. It there by explores the functions these notions have in the Herbartian teaching theory and in the Freudian theories of knowing and knowledge.